Three new Angiospermic (Orchidaceae) records from Bangladesh - Huda, Mohammed Kamrul; Hoque, Mohammed Mozammel; Alam, Md Owahidul (Jahangirnagar University Journal of Biological Sciences, 2021)
Coelogyne schwadtkii Danell., Cleisostoma williamsonii (Rchb.) Garay. and Phalaenopsis difformis (Wall. ex Lindl.) Kocyan & Schuit. of the family Orchidaceae collected from southeast part of the country have been reported here as new angiospermic records for Bangladesh flora. Detailed critical examination of the specimens of these species has been made to confirm their taxonomic identification. Detailed taxonomic description with flowering time, ecology, geographical distribution, illustration and photographs of each species has been provided. Jahangirnagar University J. Biol. Sci. 9(1 & 2): 123-132, 2020 (June & December)